A detailed examination of platelet function inhibition by nitric oxide in platelet-rich plasma and whole blood - Zimmermann, Robert; Krüger, Julia; Filipovic, Milos; Ivanovic-Burmazovic, Ivana; Calatzis, Andreas; Eckstein, Reinhold; Weiss, Dominik R. (Clinical Laboratory, 2013)
Background: The question of whether novel instruments such as multiple electrode aggregometry (MEA) can be used for measurement of the effects of nitric oxide (NO) on platelets (PLTs) has not been examined. Methods: Therefore, we compared the effects of NO concentrations (1, 10, and 100 μM) on the PLT aggregation response to ADP, arachidonic acid (AA), collagen, ristocetin, and thrombin receptor-activating peptide 6 (TRAP-6) using light transmission aggregometry (LTA) and multiple electrode aggregometry (MEA) and examined the effects of NO using the platelet function analyzer (PFA)-100™. Results: The response of PLTs to ADP and AA was strongly inhibited by all NO concentrations in LTA and MEA. The inhibition of the responses to ristocetin and collagen was detectable in MEA at lower NO concentrations than in LTA. However, the typically increasing lag phase between collagen addition and the aggregation response in the presence of NO was more obvious in LTA. TRAP caused a reproducible early response in the presence of NO in LTA which was followed by rapid PLT disaggregation, whereas even 100 μM NO did not inhibit the response to TRAP in MEA. Finally, NO prolonged the in-vitro bleeding time remarkably more in the PFA-100 collagen-epinephrin cartridge than in the collagen-ADP cartridge. Conclusions: Whole blood versus PLT rich plasma, citrate versus hirudin, and high versus low shear influenced the effects of NO. This shows that a careful selection of models and potentially a combination of different methods is appropriate for a differentiated evaluation of pharmacological or physiological mechanisms of NO-donors or of NO-inhibitors.